Антропоцентризм у тлумачних словниках - Жуйкова, Маргарита (Видавництво Львівської політехніки, 2017)
The structure of any language, and in particular its semantic subsystem, is influencedby the universality of people’s perceptual and cognitive activity regardless of their racial, cultural, social or other background. The common specific features of human cognition, which is usually referred to as anthropocentrism in language, can be found in different aspects of language and speech functioning. In this article, it is noted that general principles of human cognition have a great impact on the work of lexicographers who construct dictionary definitions. These principles include identifying an object from the continuum of perceptual information, categorizing this object, selecting relevant defining attributes within the subcategory, forming a prototype, as well as comparing the objects on the same category level. The selection of prototypes may depend both on cultural traditions, geographical or economic conditions, in which the language is formed, and on the linguistic consciousness of ordinary members of the community.
Keywords: антропоцентризм; словникова дефініція; лексичне значення; прототип; еталонний об’єкт